Chemical and microbiological assessment of house-filtered water produced by household water filtration systems - A. S. Ammar; M. G. El-Ziney; A. I. Al-Turki (Пищевые системы, 2024)
Chemical characteristics and microbiological quality of filtered water generated from municipal water using mono-, di- and penta-stage (5-stage) filters, as well as disposed drain water were investigated. With the application of the household water penta filters, the total dissolved solids (TDS) of the filtered water were highly reduced (0.04–0.07 g/L) and, consequently, electrical conductivity also decreased. Furthermore, total hardness was completely removed (0–2 mg CaCO3/L), as well as the chloride content. In the same manner, the nitrate content in the filtered water resulted from the household water penta filters decreased significantly (0.5–0.9 mg/L). Cations, such as Na+ and K+, in the filtered water were greatly affected and were 18–28 and 2 mg/L, respectively. Filtered water generated from the house-water penta filters was not in compliance with the daily amounts of F, Na and K necessary for teenagers and kids, and it might cause a risk of deficiencies. From the microbiological point of view, the penta-stage filter effectively removed total bacterial counts and total coliforms from water making it completely safe for potable and other domestic uses. The home water mono- and di- filters had low effectiveness of contaminant removal.